G494 Understanding the current landscape for ensuring equal access to high quality hospital care and services for children and young people with learning disabilities. (24th May 2017) - Oulton, K; Wray, J; Carr, L; Hassiotis, A; Jewitt, C; Kenton, C; Kerry, S; Russell, J; Tuffrey-Wijne, I; Whiting, M; Gibson, F
Abstract : Background: There has yet to be a comprehensive review of how well the needs of children and young people (CYP) with Learning Disabilities (LD) are met when accessing hospital services. Hence, we do not know whether existing recommendations, generated in response to evidence of poor experiences and outcomes for adults with LD, can and should be applied to CYP, to what extent they are being applied and if so, what difference they are making. The aim of Phase 1 of the Pay More Attention study was to map at the organisational level, the policies, systems and practices in place within specialist children's and non-specialist hospitals to support the care of CYP with LD. Methods: Semi-structured telephone interviews were conducted with senior members of hospital staff and those with a specific remit for the management of ID care. Interviews were recorded and transcribed verbatim. Framework analysis was used to synthesise practices within each hospital and compare practices across different hospitals. Results: The study sample comprised 65 staff across 22 hospitals in England. Almost half of hospitals had an electronic flagging system in place to identify CYP with LD. Participants identified a range of barriers and facilitators to identifying CYP with LD and to CYP with LD accessing services. A number described having reasonable adjustments in place for these patients; most frequently in relation to out-patient provision. At all hospitals, staff spoke about involving CYP and their families in their care and treatment, but often struggled to identify specific adjustments made to elicit their feedback and involve them in service planning. Less than a third reported having hospital information available in accessible formats. Most sites identified differences in safety issues between CYP with and without LD. Very few had a standalone ID policy or a specific mechanism for identifying CYP with LD within a complaint. Conclusion: The nature and extent of organisational policies, systems and practices in place within hospitals to support the care of CYP with LD differs widely across England. There is a pressing need to understand the subsequent impact on CYP with LD and their families.